Coupled Mechanical–Electrochemical–Thermal Study on the Short-Circuit Mechanism of Lithium-Ion Batteries under Mechanical Abuse. Issue 12 (6th August 2020) - Li, Honggang; Liu, Binghe; Zhou, Dian; Zhang, Chao
Abstract : The mechanical–electrochemical–thermal coupled failure behavior of lithium-ion batteries under external mechanical crushing has attracted a great deal of attention due to its complicated mechanism and significant safety risk. In this study, a simultaneously coupled modeling methodology incorporating mechanical, electrochemical, short-circuit, and thermal modeling is proposed for predicting the short-circuit behavior of a pouch battery under mechanical abuse. The coupled mechanical–electrochemical–thermal model includes an explicit representation of each component such as the active material, the current collector and the separator, and it predicts simultaneously the progression of short-circuit behavior during mechanical abuse. The model successfully captures the onset of a short-circuit induced by separator failure as well as the subsequent electrical and thermal responses in a reasonable manner. The modeling results elaborate the sensitivity of the voltage drop and temperature rise against the physical modes and the propagation of short circuits in a multi-cell specimen. The results also identify the importance of considering the contact area and the quantity of short circuits in the coupled simulation. The proposed model delivers useful insights for the understanding of the internal short-circuit mechanism of lithium-ion batteries under mechanical abuse.